2004
DOI: 10.1148/radiol.2302021678
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytomas: Detection with11C Hydroxyephedrine PET

Abstract: HED PET is useful in the detection of pheochromocytomas, providing a high level of accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 13 publications
1
35
0
2
Order By: Relevance
“…In this context, different tracers have been proposed to visualize NETs and the majority of these experiments have been based on the NET's capacity to take up and decarboxylate amino acid precursors (APUDomas; Pearse 1969). For example, PET using radiolabeled amine precursors, such as hydroxytryptophan (HTP; Orlefors et al 2005, Koopmans et al 2008, hydroxyephedrine (Trampal et al 2004), dopamine (Pacak et al 2001), and dihydroxyphenylalanine (DOPA), has been developed for the localization of NETs. Since the pioneering study of Ahlstrom et al (1995) using carbon-11-labeled-DOPA, a fluorine-18-labeled analogue [ 18 F]DOPA has been used for the diagnosis of carcinoid tumors (Hoegerle et al 2001b, Becherer et al 2004, Koopmans et al 2008, pheochromocytomas (Hoegerle et al 2002, Timmers et al 2007a, insulinomas (Otonkoski et al 2006, Kauhanen et al 2007, Koopmans et al 2008, medullary thyroid carcinomas (Hoegerle et al 2001a), and glomus tumors (Hoegerle et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, different tracers have been proposed to visualize NETs and the majority of these experiments have been based on the NET's capacity to take up and decarboxylate amino acid precursors (APUDomas; Pearse 1969). For example, PET using radiolabeled amine precursors, such as hydroxytryptophan (HTP; Orlefors et al 2005, Koopmans et al 2008, hydroxyephedrine (Trampal et al 2004), dopamine (Pacak et al 2001), and dihydroxyphenylalanine (DOPA), has been developed for the localization of NETs. Since the pioneering study of Ahlstrom et al (1995) using carbon-11-labeled-DOPA, a fluorine-18-labeled analogue [ 18 F]DOPA has been used for the diagnosis of carcinoid tumors (Hoegerle et al 2001b, Becherer et al 2004, Koopmans et al 2008, pheochromocytomas (Hoegerle et al 2002, Timmers et al 2007a, insulinomas (Otonkoski et al 2006, Kauhanen et al 2007, Koopmans et al 2008, medullary thyroid carcinomas (Hoegerle et al 2001a), and glomus tumors (Hoegerle et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…HED was produced as previously detailed [15,16]. A PET scanner (ECAT EXACT HR Plus, Siemens/CTI, Knoxville, Tenn., USA) was used from March 2000 to December 2004.…”
Section: Methodsmentioning
confidence: 99%
“…HED-PET has previously been evaluated for PET imaging of PHEO/PGL [13,14,15]. The additional value of HED-PET and HED-PET/CT for the clinical management of PHEO has been demonstrated in a small patient group in an early study [15], and we recently reported our 11-year experiences from a single center [16].…”
Section: Introductionmentioning
confidence: 99%
“… ñâÿçè ñ ýòèì èñïîëüçóþòñÿ äðóãèå ìåòîäû ôóíêöèîíàëü-íîãî îòîáðàaeåíèÿ. Ïðè ïðîâåäåíèè ïîçèòðîííî-ýìèññè-îííîé òîìîãðàôèè (ÏÝÒ) äëÿ äèàãíîñòèêè ôåîõðîìîöè-òîìû èñïîëüçóþò íîâûå ìíîãîîáåùàþùèå ñïåöèôè÷íûå ðàäèîíóêëèäû 6- [16][17][18][19][20][21]. Ïîñëåäíèå èññëåäîâàíèÿ ïðîäåìîí-ñòðèðîâàëè ïðåâîñõîäñòâî ýòèõ ìåòîäîâ ïî ñðàâíåíèþ ñ ñöèíòèãðàôèåé ñ ÌÈÁÃ-I 123 è ÌÈÁÃ-I 131 (17).…”
Section: ðåäàêöèîííûå ìàòåðèàëûunclassified